2016
DOI: 10.1016/j.als.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Post-fire Successions of Vegetation and Pinus koraiensis Ectomycorrhizal Communities in Korean Pine–Broadleaf Forests of the Central Sikhote-Alin

Abstract: a r t i c l e i n f o a b s t r a c t Available online xxxxThe characteristics of four stages of demutational succession of a valley Korean pine-broadleaf forest are provided according to the parameters most vividly capturing the structure of the plant community and influencing the renewal and mycorrhization of Korean pine (Pinus koraiensis) seedlings. It was found that Korean pine seedlings grow in a competitive environment on the fresh burned site; hence the mycorrhization occurs from specialized symbiotes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Accordingly, the presence of EcM fungi is vital for the establishment of ob li ga to ry mycorrhizal framework in recurring P. koraiensis phytocoe noses, where fireresistant EcM fungi or fungi with rapid recolonization strategy from available sources of inocu lum acquire great importance. To the best of our know ledge, this is the first resumptive study, which gene ra lizes all information of the belowground EcM community of P. koraiensis growing in the Central SikhoteAlin moun tains (Malysheva et al 2014, Pimenova et al, 2015. At the four study sites we distinguished 110 EcM fungal ta xa based on analyzing of P. koraiensis mature trees and seedlings root tips.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, the presence of EcM fungi is vital for the establishment of ob li ga to ry mycorrhizal framework in recurring P. koraiensis phytocoe noses, where fireresistant EcM fungi or fungi with rapid recolonization strategy from available sources of inocu lum acquire great importance. To the best of our know ledge, this is the first resumptive study, which gene ra lizes all information of the belowground EcM community of P. koraiensis growing in the Central SikhoteAlin moun tains (Malysheva et al 2014, Pimenova et al, 2015. At the four study sites we distinguished 110 EcM fungal ta xa based on analyzing of P. koraiensis mature trees and seedlings root tips.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the coenopo pu la tion structure and dynamics showed that the group of ini tial species, the most active in the early years after the fire, Figure 5 OTUs numbers in relation to soil layers (A 0 -AB) and the age of the Pinus koraiensis trees at different sites was only 10 % of the total number of species, and se rial and climax coenopopulations reached a significant di ver sity (Pimenova et al 2015). Initial coenopopulations are repre sented by annualbiennial herbs and shrubs with a circum polar, Eurasian and AsianNorth American dis tri bution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation